Efficacy and long-term safety of C.E.R.A. maintenance in pediatric hemodialysis patients with anemia of CKD - Fischbach, Michel; Wühl, Elke; Schaefer, Franz (Clinical journal of the American Society of Nephrology, 2018)
Background and objectives The study was conducted to identify a conversion factor for switching from previous erythropoiesis-stimulating agents (ESAs) to continuous erythropoietin receptor activator-methoxy polyethylene glycol-epoetin beta (C.E.R.A.) and to document the efficacy and long-term safety of C.E.R.A. in pediatric patients with anemia of CKD undergoing hemodialysis. - Design, setting, participants, & measurements In this open-label, multicenter study, patients aged 6-17 years, with stable chronic anemia of CKD, undergoing hemodialysis received C.E.R.A. every 4 weeks, at a starting dose determined by previous weekly epoetin alfa/beta or darbepoetin dosing. After a 16-week dose-titration and a 4-week evaluation period, patients with stable hemoglobin could enter a 1-year optional safety extension. - Results A total of 64 patients were enrolled. A conversion factor (4 µg every 4 weeks for each weekly dose of 125 IU epoetin alfa/beta or 0.55 µg darbepoetin) was identified that allowed patients to maintain hemoglobin within target levels on switching to C.E.R.A. from another ESA. Using this conversion factor, the adjusted mean change in hemoglobin from baseline to evaluation was −0.09 g/dl (95% confidence interval, −0.45 to 0.26); 81% of patients maintained hemoglobin within 10.0-12.0 g/dl and 75% maintained hemoglobin within 1.0 g/dl of baseline. Results were consistent across age groups (6-11 and 12-17 years) and previous ESA. Thirty-seven patients entered the safety extension period and 17 completed 73 weeks of treatment. Most withdrawals were for kidney transplantation. A total of 70% of patients had hemoglobin within 10.0-12.0 g/dl at last observation, and 62% were within ±1.0 g/dl of baseline. Safety was similar to studies in adult patients, with no new signal detected. - Conclusions Using a defined conversion factor, 4-weekly C.E.R.A. was efficacious in maintaining hemoglobin levels in pediatric patients with stable anemia of CKD undergoing hemodialysis, switching from maintenance treatment with epoetin alfa/beta or darbepoetin. Safety was consistent with the known C.E.R.A. safety profile in adults.
Gesehen am 14.05.2020